Phylogenomic analysis of Xylella fastidiosa subsp. pauca strains from olive and almond trees in Argentina - Fernandez, Franco Daniel; Arias-Giraldo, L.F.; Tolocka, Patricia; Guzman, Fabiana; Olivares García, C.; Roca, M.E.; Otero, Maria Laura; Conci, Luis Rogelio; Landa, B.B.; Haelterman, Raquel Mercedes (Springer, 2025)
Xylella fastidiosa (Xf) is a Gram-negative bacterium that significantly threatens agricultural crops worldwide. In Argentina, severe symptoms resembling those of olive quick decline syndrome (OQDS) in Italy have been observed in Xf-infected olive orchards, primarily affecting the 'Arauco' variety in La Rioja province. All Xf strains identified in Argentina, up to now, belong to the subspecies pauca (Xfp), with two sequence types (ST69 and ST78) identified so far. In this study, the complete circularized genomes of three Xf strains, isolated from olive (OLI17A, AM2-Angelina; from ST 69) and almond (ALM4; from ST78) infected trees in different regions in Argentina, were obtained using a hybrid assembly approach combining Oxford Nanopore Technologies and Illumina sequencing. Comparative genome analysis revealed collinearity between two strains (AM2-Angelina and OLI17A), while the ALM4 strain exhibited a large chromosome inversion in comparison to the AM2-Angelina and OLI17A genomes. The three genomes encoded numerous virulence genes involved in twitching motility and adhesion; although strain ALM4 lacked some anti-virulence factors such as prtA gene. Plasmids similar to those found in Xf strains isolated from citrus in South America and from olive trees in Europe were also identified. Comparative genomic analysis and phylogenetic reconstruction showed that the Xf Argentinean strains were genetically differentiated from those found in other countries although they formed a monophyletic group within the Xfp strains sequenced so far. Indeed, they were closely related to strains from citrus previously reported in Argentina and Brazil. The availability of these genomes will provide valuable insights for future studies on comparative genomics, virulence mechanisms, and epidemiology of Xf outbreaks in Argentina and elsewhere.